The Role of the State Social Protection System in Stabilizing the Society Environment (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, it is socio-philosophically researched that the social protection system is a process that should be followed by incorporating not only spiritual and moral qualities, but also important social problems that need to be solved urgently in the current market economy. In this, it is revealed that the goal of the state social economic policy and its comprehensive support are interconnected, and they complement each other and serve to ensure the well-being of life in the environment of that society. A strong social protection system is the basis of stability in the social environment, and it is represented by the main functions of the state in social protection and its implementation in the market economy, social justice and guidelines for its resolution, existing conflicts and their rational solutions.